2020
DOI: 10.4178/epih.e2020039
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for low back pain among the elementary school students, using penalized logistic regression, Iran

Abstract: According to the 2017 Global Burden of Disease study, low back pain (LBP) was ranked first among health issues in terms of years lived with disability (YLDs) [1]. It is also the second highest cause of YLDs among 15-19-year-old, accounting for more YLDs than other health problems, such as asthma, alcohol consumption, drug use, and road traffic injury [2]. LBP is a prevalent condition among school-age students, but it has not received sufficient attention [3]. In developing countries such as Thailand, Zimbabwe,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 43 publications
(61 reference statements)
0
8
0
1
Order By: Relevance
“…This phase comprises predisposing factors (knowledge, attitudes, perceptions, beliefs), reinforcing factors (family, peer, teacher influences) as well as enabling factors (availability of resources, skills) [ 22 ]. Some studies, including the studies, done by the research team of current study, reported high prevalence of musculoskeletal pains and effects of some risk factors and predictors on them [ 23 , 24 ]. Some of these predictors are knowledge and beliefs of care for back and spine, posture and ergonomics and other cognitive factors like perceived self-efficacy, perceived benefits, perceived barriers and intention behavior [ 7 , 25 – 28 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This phase comprises predisposing factors (knowledge, attitudes, perceptions, beliefs), reinforcing factors (family, peer, teacher influences) as well as enabling factors (availability of resources, skills) [ 22 ]. Some studies, including the studies, done by the research team of current study, reported high prevalence of musculoskeletal pains and effects of some risk factors and predictors on them [ 23 , 24 ]. Some of these predictors are knowledge and beliefs of care for back and spine, posture and ergonomics and other cognitive factors like perceived self-efficacy, perceived benefits, perceived barriers and intention behavior [ 7 , 25 – 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…This study is part of a larger research project conducted on musculoskeletal pain and its risk factors [ 23 , 24 ]. We found that backpack carrying behaviors and the sitting postures were among the factors associated with musculoskeletal pain, so in the present study we examined the factors associated with these two important behaviors, using Health Promotion Models including PRECEDE and Health Belief.…”
Section: Introductionmentioning
confidence: 99%
“…The binary logistic regression results we present further strengthen the evidence that lifetime prevalence of LBP increases with age, with an odds ratio (OR) of 2.1 (95% CI= 1.36–2.86) for older age, in agreement with earlier findings [ 2 , 7 , 9 ]. For instance, in Rezapur-Shahkolai et al [ 26 ], students (7–12 years old) reported LBP in the last month, with an OR of 3.08 (95% CI: 1.80–5.26) for older age.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of previous researches on the topic of carrying a school bag for school-age children have been focused on the identification of risk factors that are related to weight, back curvature, the presence of pain, exhaustion and the appearance of fatigue using statistical indicators. [20][21][22][23][24][25] However, a small number of authors considered that the role of parents in solving this problem is crucial [26][27][28] and that it can significantly contribute to ensuring unhindered growth and development during the child's educational process.…”
Section: Discussionmentioning
confidence: 99%